Effectiveness of Empowerment Micro Enterprise - Mutmainah, Isbandriyati (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2015)
This research aims to analysis the effectiveness of micro enterprise empowerment through P3KUM assistance, with research sites in the Bogor District. Descriptive analysis is used to see micro enterprise characteristic, chi-square test to see micro-business opportunities to get the help, and Wilcoxon Signed Rank Test to see the effectiveness of micro enterprise empowerment. The opportunities for small business long viewed from different business, product type, and type of business. While aid effectiveness viewed from difference between before and after efforts to get aid. A research result shows micro-enterprise opportunities for assistance varies. When viewed from old business, micro-business opportunities for assistance are the same. Meanwhile, if viewed from product type that produce and type of business, micro-business opportunities for assistance are the different. P3KUM aid significantly increase the effectiveness to produce, increase added value, and able to increase capital productivity but able not to increase labor productivity.